ELECTRIC SYSTEMS IN SULA ELECTRIC CARS IN SULA ELECTRIC CARS' SUBANG STATE POLYTECHNIC - Adhan Efendi (VANOS Journal of Mechanical Engineering Education, 2020)
The making of electric cars in POLSUB is intended to be further developed by the junior level and as a medium for applying the electrical system to SULA electric cars. The right method for applying the electrical system to Sula's electric car16 is by reading the wiring diagram. Wiring diagram reading is useful to produce a neatly arranged wiring system and can reduce the obstacles contained in the electrical system in electric cars Sula. The results obtained from electrical installations on electric cars Sula produce a final voltage of 49.79 and watt hours 53,2 in a distance of 10 Km. From these results it can be concluded that the electric car is included in the category of energy saving.